Deconstructing Village Law through Maqasid al-Shari'ah: An Indonesian Legislative Study - Risqi Dafiro; Busriyanti Busriyanti (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
This study employs a library research method to examine the formulation of Law Number 6 of 2014 concerning Villages through the lens of Maqashid Syariah, the objectives of Islamic law. The law is recognized as reflecting strong Islamic values, consistent with the perspective of Imam Al-Ghazali, who emphasized that Islamic law aims to achieve the well-being and happiness of humanity both in this world and the hereafter. The five key components of Maqashid Syariah protection of religion (hifdz ad-din), life (hifdz an-nafs), intellect (hifdz al-‘aql), lineage (hifdz an-nasb), and property (hifdz al-maal) serve as the evaluative framework in this analysis. The research findings indicate that the establishment of Law Number 6 of 2014 was intended to enhance the effectiveness of village governance, improve public service delivery, strengthen community empowerment, and encourage active citizen participation in national development. The law provides maslahah (public benefit) by addressing the universal needs of society and aligning with the principles of Maqashid Syariah. Additionally, the study affirms that the law not only benefits Muslims but also serves the interests of non-Muslim communities, thereby reinforcing the universal applicability of Islamic legal values. The analysis concludes that the integration of Maqashid Syariah into legislative processes, as demonstrated by this law, supports the development of regulations that are comprehensive, inclusive, and beneficial to society. It also underscores the role of Islamic legal philosophy as a valuable standard for law-making aimed at achieving sustainable and widespread societal welfare.